Estimate of soybean defoliation via digital image processing in software - Nabeyama Michels, Roger (Revista Ciência Agronômica, 2021)
This study aimed to develop and validate the digital image processing software to quantify leaf coverage, employingthe correlation of defoliation values and NDVI with various gradients of defoliation severity of the Asian soybean rust pathosystem.The digital images were obtained from the experiment conducted in 2013/2014. To conduct the experiment, 4 treatments (3 replicates)were adopted, considering the useful fl oor area of each plot (4 linear meters, 3 lines spaced at 0.45 m). The gradients of defoliation wereobtained by treatment with fungicide to control Asian soybean rust. The quantifi cation of the disease severity was performed throughdiagrammatic scale. The NDVI values were obtained using the GreenSeeker®, conducting the equipment above the plants. The digitalphotos were obtained in three heights and subsequently processed in software. Then the defoliation sampling was held in 10 plants throughtreatment. The image processing data correlated with defoliation (94.22%) and with NDVI (89.27%), and we also observed the correlationof defoliation with NDVI (96.12%). These data suggests the use of digital images as an alternative to quantify the vegetation cover, withthe advantage of being a dynamic and fast method that does not require experience from the assessor to quantify soybean defoliation.